2005
DOI: 10.1002/ajh.20328
|View full text |Cite
|
Sign up to set email alerts
|

Reduction in coagulation factor VII plasma levels by R353Q but not the −323P0/10 promoter polymorphism in healthy Tunisians

Abstract: The association between the R353Q and -323P0/10 (10-bp insertion in the promoter region at position -323) factor VII mutations and plasma factor VII levels was investigated in a group of 214 healthy Tunisians. The frequency for the Q allele was 0.253 and that for the 10-bp allele was 0.206, and their distribution was variable, with a high prevalence of the 10-bp allele (0.306) seen in North Tunisia and a high prevalence of the Q allele (0.288) seen in the Sahel region. No significant linkage disequilibrium was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 35 publications
1
9
0
Order By: Relevance
“…A few Tunisian studies were interested in the distribution of some polymorphisms (M1/M2 and P0/P10) in patients with FVII deficiency and healthy groups from different Tunisian regions demonstrate that the most frequent alleles are M1/M1 and P0/P0 in all the studied groups and also in groups from the North of Tunisia [4,5]. This distribution is confirmed in our patients who are from the North and in whom we identified only one allele M1/M2 in one patient/7 unrelated patients and we found the allele P0/P10 only in 2 patients.…”
Section: Discussionmentioning
confidence: 99%
“…A few Tunisian studies were interested in the distribution of some polymorphisms (M1/M2 and P0/P10) in patients with FVII deficiency and healthy groups from different Tunisian regions demonstrate that the most frequent alleles are M1/M1 and P0/P0 in all the studied groups and also in groups from the North of Tunisia [4,5]. This distribution is confirmed in our patients who are from the North and in whom we identified only one allele M1/M2 in one patient/7 unrelated patients and we found the allele P0/P10 only in 2 patients.…”
Section: Discussionmentioning
confidence: 99%
“…1, two heterozygous mutations in the F7 gene of the patient were identified by direct genomic DNA sequencing, including a G-to-A transition at nucleotide 15975 in the splice receptor site of intron 6 (IVS6-1G>A) and a C-to-T transition at nucleotide 16750 in exon 8 with the substitution of Ser (TCC) for Phe (TTC) at amino acid 190 (p.Ser190Phe). The rare polymorphisms of F7 lowering plasma levels were not detected [10][11][12]. The patient's mother was heterozygous for F7 15975 G>A (IVS6-1G>A), whereas his father was heterozygous for in F7 were found in his sister and no other variants were found in this family.…”
Section: Coagulation Assaysmentioning
confidence: 98%
“…Most of the data have shown that the insertion of a decanucleotide fragment at position −323 in the promoter region of FVII is related to lower coagulation activity and antigen level of factor VII (10,41,42). On the other hand, Mtiraoui et al (43) did not find such correlation in a population of healthy Tunisians. The elevated activity of factor VII may indicate a tendency for thrombosis, thus suggesting that a decreased level of circulating factor VII may exert a protective effect on their development.…”
Section: Discussionmentioning
confidence: 84%